2018
DOI: 10.2478/jbe-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Properties, Structural Characteristics and Application Potentials of Concrete Containing Wood Waste as Partial Replacement of one of its Constituent Material

Abstract: There is a growing concern that the sustainability of our built environment is being endangered, due to the uncontrolled and massive use of non-renewable natural resources in the production of structural concrete that is used for the construction of her infrastructure. Alternative material resources are being discovered through myriads of research efforts to address this concern. One of such alternative materials is the wood waste material. This paper presents a comprehensive review of properties, structural b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…According to Fapohunda et al [106], using wood waste as SDA, or sawdust, in a suitable concrete mix design can provide structural concrete that conforms with building conditions. SDA content, nevertheless, cannot outstrip 20%.…”
Section: Use Of Sawdust Ash (Sda) As Replacement Of Cementmentioning
confidence: 99%
“…According to Fapohunda et al [106], using wood waste as SDA, or sawdust, in a suitable concrete mix design can provide structural concrete that conforms with building conditions. SDA content, nevertheless, cannot outstrip 20%.…”
Section: Use Of Sawdust Ash (Sda) As Replacement Of Cementmentioning
confidence: 99%
“…The compressive strength, on the other hand decreased in relation to the control with increase in the percent replacement of cement with SDA (Udoeyo et al, 2006 andRaheem et al, 2012). However, the numerical values of compressive strength obtained from cube tests by researchers, as presented by Fapohunda et al (2018) in Table 6, suggested that SDA can be incorporated into the concrete mixes to develop the required strength specified by various international standards. However, at the curing ages of 90 days, the results of Ghorpade (2012) showed improved compressive strength over the control samples at replacement levels up to 30%.…”
Section: ) Hardened State Propertiesmentioning
confidence: 99%
“…Fapohunda et al [83] showed that, wood waste, either in the form of SDA, or wood aggregate, or sawdust; can be incorporated into an appropriate concrete mix design which can yield structural concrete that satisfies building requirements. The SDA content must however, not exceed 20%.…”
Section: Partial Replacement Of Cement With Sawdust Ash (Sda) In Thementioning
confidence: 99%